Efficacy of Lemna minor and Typha latifolia for the treatment of textile industry wastewater in a constructed wetland under citric acid amendment: A lab scale study. (November 2021) - Ishaq, Hafiz Khuzama; Farid, Mujahid; Zubair, Muhammad; Alharby, Hesham F.; Asam, Zaki Ul Zaman; Farid, Sheharyaar; Bamagoos, Atif A.; Alharbi, Basmah M.; Shakoor, Muhammad Bilal; Ahmad, Sajid Rashid; Rizwan, Muhammad; Ali, Shafaqat
Abstract: Lead (Pb), copper (Cu) and chromium (Cr) are one of the most harmful heavy metals (HMs), entering into the food chain through the irrigation of crops with an industrial effluent. The present study was performed to evaluate the toxic effects of textile effluents and performance of citric acid (CA) on phytoextraction potential of Lemna minor L. and Typha latifolia L. in an artificially designed wetland. Different doses of textile wastewater (0, 25, 50, 75, and 100%) and CA (10 mM) were applied alone and in combination. Plants were harvested and the data was collected regarding agronomic traits, photosynthetic pigments, antioxidant enzymes, reactive oxygen species (ROS), electrolytic leakage (EL) and HMs uptake and accumulation. The results depicted that the concentration and accumulation of Cu, Pb and Cr in different parts of T. latifolia plant was increased with and without CA addition. The maximum concentration of Pb, Cu and Cr increased in leaves by 279, 240 & 171%, in stem by 192, 172 & 154%, and in roots by 224, 183 & 168%, respectively. Similarly, the accumulation of Pb, Cu and Cr increased in leaves by 91, 71 & 36%, in stem by 57, 46 & 36% and in roots by 76, 53 & 45%, respectively in plants treated with 100% textile effluent as compared to the 25% textile effluent treated plants under CA amendment. In L. minor, the concentration of Pb, Cu & Cr increased by 542, 411 and 397% while accumulation increased by 101, 59 & 55% respectively in overall plant biomass. Graphical abstract: Image 1 Highlights: Textile industry effluents contained increased level of heavy metals. Heavy metal stress reduced the growth and biomass of T. latifolia and L. minor . CA enhanced photosynthetic pigments and antioxidant enzymes activities. CA enhanced the bioavailability and accumulation of Pb, Cu and Cr. T. latifolia and L. minor showed higher efficacy for textile effluent treatment under CA.